Production, yield and area growth of major winter vegetables of Bangladesh: Growth and trend of major winter vegetables (Journal of the Bangladesh Agricultural University, 2018)
Winter vegetable production has increased tremendously in Bangladesh. Excessive supply of vegetables reduces the market price that leads to economic loss at farm level. This study  assesses the growth and trend of winter vegetables production, yield and area in Bangladesh. Semi-log regression model was used to assess the growth and trend of winter vegetables while Winston Prais transformation was utilized to solve the autocorrelation problem. Yearly time series data of collected from secondary sources was used for this analysis. Data were collected from 1986–87 to 2015–16 years. Data of some major winter vegetables like tomato, rabi brinjal, rabi pumpkin, water gourd, cauliflower, cabbage, radish, bean, green spinach were collected for this study. Results found that growth of tomato, cauliflower and cabbage production was about 5% which was much higher than other winter vegetables. Growth of cultivated area is about 3% per annum for most of the vegetables. Production of winter vegetables increases because of yield and area growth. Government can attempt to increase export of tomato, cauliflower and cabbage. Moreover, yield growth of green spinach and radish is necessary to increase both production and export.J. Bangladesh Agril. Univ. 16(3): 492–502, December 2018